Implications of the New Rule Against Penalties - Palmer, Jessica (Victoria University of Wellington Law Review, 2016)
Whether a contractual term is penal and therefore unenforceable has usually been determined by distinguishing it from stipulations that are a reasonable contemplation of loss resulting from breach. This article considers recent decisions of the High Court of Australia and the United Kingdom Supreme Court that have made significant revisions of the rule. Both Courts have diverged from the traditional formulation and, to some extent, from each other. I argue that the traditional rule against penalties reflects foundational principles of contract law and not merely notions of fairness or justice in the round. The recent revisions to the rule have implications for the role and boundaries of contract law more generally and reflect increasing attention being paid to the "performance interest".